2004
DOI: 10.1128/jcm.42.11.5053-5057.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium africanumGenotyping UsingNovel Spacer Oligonucleotides in the Direct RepeatLocus

Abstract: This study involves a first evaluation of 25 novel spacer oligonucleotides in addition to the 43 routine spacers for molecular characterization of a panel of 65 isolates of tubercle bacilli from different geographic origins that were initially classified as Mycobacterium africanum based on phenotypic characters. The 68-spacer format defined four additional patterns, and three groups were identified. The relatively homogeneous groups A1 and A2 included strains from West Africa, and A3-1 included strains from Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
(31 reference statements)
4
27
0
Order By: Relevance
“…Hence, our data support the call to do away with the unnecessary "subtype II/East African/M. tuberculosis-like" M. africanum designation (1, 23) since, in every case reported to date, strains identified as such were later found to really be either M. tuberculosis PGG1 or PGG2 isolates rather than true M. africanum when reevaluated by molecular means (1,2,13,19,20).…”
Section: Resultssupporting
confidence: 73%
“…Hence, our data support the call to do away with the unnecessary "subtype II/East African/M. tuberculosis-like" M. africanum designation (1, 23) since, in every case reported to date, strains identified as such were later found to really be either M. tuberculosis PGG1 or PGG2 isolates rather than true M. africanum when reevaluated by molecular means (1,2,13,19,20).…”
Section: Resultssupporting
confidence: 73%
“…These spacers were found to increase the ability of spoligotyping to discriminate between M. bovis, M. caprae, and M. microti strains and also showed polymorphisms between strains of the M. tuberculosis Beijing genotype (34,71,73). In a recent study by Brudey et al (11) it was shown that the additional spacers enhanced the ability of spoligotyping to differentiate between M. africanum isolates. In the present study we found that the inclusion of these novel spacers did not improve the overall discriminatory power of the method in comparison with the traditional spoligotyping when applied to 90 isolates of mainly M. tuberculosis.…”
Section: Discussionmentioning
confidence: 94%
“…In the previous study the species were determined on the basis of a combination of biochemical testing and DNA typing (36). However, identification of mycobacterial strains has since improved by the use of chromosomal deletions (10,28,44,48), SNPs (28), and sequencing of the 16S rRNA gene DNA (8,33 (11,44,45). The latter designation was established after revision of the interpretative guidelines used for analysis of genetic data (44).…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a first attempt to provide insight into the population structure of M. tuberculosis in Egypt. We selected spoligotyping to create this snapshot, as it has been shown to be a valuable method for determination of the clonal and phylogenetic relationships of M. tuberculosis strains, providing in parallel useful information about TB in a given population, in a given country, among countries, and throughout the world (4,5,9,10,12,16,17,19 Detailed spoligotyping results are summarized in Tables 2 and 3, while the evolutionary relationships of the strains are illustrated in an MST shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%